Da condição do lugar à harmonia compositiva. Casa al Parco, Ignazio Gardella - Verónica Isabel Marques Ferreira (2022)
Nestled at the reflection of the Modern Movement, an anchor in the contemporary way of thinking and working, the present investigation focuses on the analysis of a unique piece of architecture and its author - Casa al Parco, in Milan, by the architect Ignazio Gardella. The personal archive of the architect was set as a starting point while the study intends to understand the evolution of the design process, to analyse and clarify the different phases of development, its design options, guiding principles and architectural composition themes. As the investigation develops, the purpose is to fully understand the architect's design methods and strategies, as Gardella became an icon of a timelessness way of thinking and designing which played a crucial role on the influence of modern architecture in the contemporary narratives.